Evaluation of polypropylene/clay nanocomposite foamability based on their morphological and rheological aspects. (September 2018) - Dutta, Anindya; Sankarpandi, Sabapathy; Ghosh, Anup K
To identify the effect of rheological influence on the development of microstructure in polypropylene/clay nanocomposites and thereby the influence of the developed microstructure on the foamability of the nanocomposites, a set of nanocomposites was prepared and batch foamed using supercritical CO2 . Polypropylene and nanoclay were selected for preparing nanocomposites. During foaming, the nanocomposites were saturated with CO2 gas for three different time periods and subsequently in-situ heating was done to achieve cell growth. The gas saturation was done at subcritical condition followed by the foaming at critical condition of CO2 . Thermal studies of the composites were investigated through differential scanning calorimetry, and clay dispersion morphology was investigated and validated using wide-angle X-ray diffraction, transmission electron microscopy, and parallel plate rheology. The improvement in foam morphology (cell size and cell density) and subsequent reduction in foam density was analyzed. The fingerprint characteristics of nanocomposites have an enormous role on foam structure development. With the increase in clay loading, cell density increased; furthermore, with an increase in saturation time, there was a phenomenal decrease in expansion ratio of neat polypropylene due to CO2 -induced crystallization which could be mitigated by the incorporation of nanoclay into the polypropylene matrix. Therefore, nanoclay could be exploited as the inhibitor of CO2 -induced crystallization.